Suoni e musica nei videogiochi: dal ruolo passivo al ruolo inter-attivo nel gameplay (Connessioni remote. Artivismo_Teatro_Tecnologia, 2025)
This contribution analyses the evolution of the role of sound and music in video games, focusing on recent developments in sound design in the field of game studies. Through a brief historical overview, it highlights how sound, initially with a passive and accessory function, has taken on an increasingly active and interactive role. From Space Invaders in the 1980s to contemporary titles, sound and music have become central elements of the gaming experience. Orchestral tracks, songs and jingles now accompany both cutscenes and gameplay, contributing to a deeper sensory immersion and dynamically signalling the player's actions. Two main interactive dynamics have been identified: the use of binaural audio, which amplifies orientation and immersion by creating a sound space parallel to the visual one; and the use of sound as a narrative tool and game mechanic, especially in contexts where the image is reduced or absent. In this context, sound is conceived as “pure action”, generated by the player's inputs. The case studies analysed include Horizon Zero Dawn for the role of jingles in gameplay; Hellblade: Senua's Sacrifice and Resident Evil 2 Remake for binaural audio; Perception and Three Monkeys for sound as an interactive driver of narrative.
Keywords: Video games; interactivity; sound; music; sound design